COVID-19 has seen three approaches from the perspective of the Brazilian National Civil defense - Marcelo D’Alexandro Hoelbriegel, Anderson; Luis Belchior dos Santos , Alexandre; Frederico Cabral de Oliveira, Eduardo (Seven Editora, 2023)
QUESTIONING: What was the role of the Brazilian National Civil Defense in confronting COVID-19? OBJECTIVE: Check, along with the works produced on Civil Defense, the role of the Brazilian National Civil Defense in the fight against COVID-19, seen through three coping approaches. DOI: https://doi.org/10.56238/tfisdwv1-013